2005
DOI: 10.4049/jimmunol.174.9.5324
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of IFN-Induced Protein 10 and Its Receptor CXCR3 in Myasthenia Gravis

Abstract: Myasthenia gravis (MG) and its animal model, experimental autoimmune MG (EAMG), are autoimmune disorders in which the acetylcholine receptor (AChR) is the major autoantigen. Microarray technology was used to identify new potential drug targets for treatment of myasthenia that would reduce the need for the currently used nonspecific immunosuppression. The chemokine IFN-γ-inducible protein 10 (IP-10; CXCL10), a CXC chemokine, and its receptor, CXCR3, were found to be overexpressed in lymph node cells of EAMG rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 41 publications
6
58
0
Order By: Relevance
“…Like CCL21, CCL19 acts through CCR7, but no up-regulation of CCL19 was observed. An increased expression of CXCL10, a chemoattractant for activated T cells, was also detected, as previously described (23). However, we did not notice any MH-specific increase in the expression of CXCL12 known to contribute to the T cell homing and GC organization (22,24).…”
Section: Analysis Of the Genes Characterizing The Hyperplastic Thymussupporting
confidence: 60%
“…Like CCL21, CCL19 acts through CCR7, but no up-regulation of CCL19 was observed. An increased expression of CXCL10, a chemoattractant for activated T cells, was also detected, as previously described (23). However, we did not notice any MH-specific increase in the expression of CXCL12 known to contribute to the T cell homing and GC organization (22,24).…”
Section: Analysis Of the Genes Characterizing The Hyperplastic Thymussupporting
confidence: 60%
“…Expression of IP-10 and its receptor CXCR3 has been shown to be associated with the development of several Th1-type human inflammatory diseases, including psoriasis, multiple sclerosis, atherosclerosis, rheumatoid arthritis, and myasthenia gravis (41)(42)(43)(44)(45)(46). In addition, elevated IP-10 gene expression has been found in association with rejection of human cardiac allografts and mouse cardiac, small bowel, and pancreatic islet allografts (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 is induced by LPS in RAW macrophage cells [20]. Feferman et al [21] found increased expression of Cxcl10 and its receptor, Cxcr3, in lymph node cells of rats with experimental autoimmune myasthenia gravis. In the present study, Cxcl10 expression increased 10.50 fold in response to LPS treatment, but decreased −7.54 fold in response to melatonin treatment.…”
Section: Discussionmentioning
confidence: 99%